2017
DOI: 10.1016/j.tcr.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of TASER-induced trauma

Abstract: A young adult male experienced penetrating globe injury due to a Thomas A. Swift Electric Rifle (TASER). Despite successful repair of the globe, the damage was profound. This case report explores the complex ways in which mechanical and electrical forces from a TASER may impact the structural integrity and the neurosensory structures of the eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Seth et al reported the case of a 35‐year‐old man who sustained a minor skin burn on the left upper eyelid after being tased and a week after developed a left eye cataract (Seth et al, 2007 ). Since then, several case reports have described how Tasers may cause eye injury without direct globe trauma (Gapsis et al, 2017 ; Moysidis et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Seth et al reported the case of a 35‐year‐old man who sustained a minor skin burn on the left upper eyelid after being tased and a week after developed a left eye cataract (Seth et al, 2007 ). Since then, several case reports have described how Tasers may cause eye injury without direct globe trauma (Gapsis et al, 2017 ; Moysidis et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the eyes and surrounding area is among the most frequently reported injuries caused by penetration by darts and barbs. Out of 15 such cases reported, at least three resulted in removal of the eye or parts of the eye (enucleation or evisceration) due to irreversible damage with loss of vision, and in others there was a substantial reduction of vision (Chen et al, 2006;de Runz et al, 2014;Gapsis et al, 2017;Han et al, 2009;Jey et al, 2016;Li & Hamill, 2013;Moysidis et al, 2019;Ng & Chehade, 2005;Rafailov et al, 2017;Sharabura et al, 2021;Teymoorian et al, 2010). In one lucky incident, the eye hit was the one where a person already had an implant, whereas the only seeing eye was spared (Moysidis et al, 2019).…”
Section: Eyes and Surroundingsmentioning
confidence: 99%
“…The patient was recommended surgical consultation due to repetitive abscesses secondary to prolonged retention of the TASER dart. There is sparse reporting of TASER‐associated penetration in the literature; however, they include intracranial, ocular and distal phalanx involvement 3,5–9 . All published cases required unique operative management to remove the probe.…”
Section: Figurementioning
confidence: 99%
“…There is sparse reporting of TASER-associated penetration in the literature; however, they include intracranial, ocular and distal phalanx involvement. 3,[5][6][7][8][9] All published cases required unique operative management to remove the probe. A lesson learnt from a neurosurgical team who attempted bedside removal subsequently required the emergent need for theatre due to breaking of the probe from the barb.…”
mentioning
confidence: 99%